SEKURITILULUSSYARIAH DAN KEPENTINGANNYA KEPADA PASARAN MODAL ISLAM - Md Yusof, Syarifah (Jurnal Syariah, 2019)
This article will discuss Shariah approved securities and its significance to the development of Islamic capital market in Malaysia. It tries to explain the criterion set up by ShariahAdvisory Council of Securities Commission for screening the securities trading in Bursa Malaysia as well as some issues regarding the criterion itself. It is found that the list of Shariah approved securities benefits Muslim investor and enhances the development of Malaysian Islamic capital market as well.